Faktor Pendukung dan Penghambat Peran Pendampingan Suami Terhadap Isteri Pada Masa Kehamilan dan Persalinan - Theresia Limbong (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; the role of husband's assistance is still a socio-medical problem both at the global level and at the national and local levels. Aim; examine the factors supporting and inhibiting the role of husband's assistance to his wife during pregnancy and childbirth. Method; qualitative descriptive methods, exploratory and phenomenological studies. Data sources are primary and secondary data. Data collection techniques include observation, interviews, and documentation. The main instrument of the research is the author himself, supported by interview guides, recording, recording, and validating data, and field recording equipment, tape recorders, digital cameras. Data analysis models are carried out interactively and continue continuously until complete. The series of processes include data reduction, data presentation, and data verification. Results; that social structure, social actors (including empathy, positive perception, motivation, belief values, attitudes, social competence, and social behavior), family support, multidimensional changes in the wife, problem-solving, and conflict needs, are all supporting factors. Meanwhile, time, space, occupation, negative perception, frequency of pregnancy and childbirth, workplace policies, policies in health care centers, and wife's behavior are inhibiting factors. Conclusion; that the supporting factors for the role of husband's assistance to his wife during pregnancy until delivery are: social values ​​and norms; social factors, family support; multidimensional changes in the wife; and problem-solving and conflict needs